2017
DOI: 10.12659/msm.905718
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy Rates of Thyroid Cytology: Cyst Fluid Benign or Non-Diagnostic?

Abstract: BackgroundWe sought to investigate subgroup distribution using Bethesda classification and risks for malignancy. We also compared the malignancy risk of cases that were denoted as non-diagnostic due to cystic contents, with cases that were denoted as non-diagnostic due to presence of other features.Material/MethodsThe study included pathology test results of 1,440 thyroid nodule samples diagnosed using Bethesda classification. Results of 305 thyroidectomy excision specimens from these patients were also compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…We excluded a further 233 studies and finally selected 38 studies, which included 145,066 thyroid nodules, for meta‐analysis (Fig. ) . Among the included studies, 4 were prospective and 34 were retrospective.…”
Section: Resultsmentioning
confidence: 99%
“…We excluded a further 233 studies and finally selected 38 studies, which included 145,066 thyroid nodules, for meta‐analysis (Fig. ) . Among the included studies, 4 were prospective and 34 were retrospective.…”
Section: Resultsmentioning
confidence: 99%
“…The risk in mixed lesions is up to 15% [11] . A recent study also reported that cystic lesions regarded as non-diagnostic on FNA are more prone to be benign [12] . We found nodules with cystic degeneration only in one patient, but this could not be understood on PE.…”
Section: Discussionmentioning
confidence: 93%
“…The ROM of CFO nodules have reportedly ranged from 0% to 14.3% 6,[16][17][18]. Güney and Şahiner reported that, in their study, malignancy was not detected in any of the specimens taken from 14 out of 48 patients who were diagnosed with CFO nodules and had undergone operations 8. According to a report by Jaragh et al, of the 76 CFO cases with subsequent thyroidectomy, 10 cases (13.2%) had an ipsilateral diagnosis of papillary carcinoma measuring ≥1.0 cm 7.…”
mentioning
confidence: 83%
“…5 Thus, CFO nodules have two different clinical managements that can be determined based on ultrasound findings. To date, the availability of extensive research focusing on CFO nodules is limited, [6][7][8] and the ROM in CFO nodules has not been well established. The purpose of the current study was to review cytological and ultrasound findings of CFO nodules, define the ROM, and determine the recommended clinical management of CFO nodules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation